Venlafaxine-induced serotonin syndrome causing bilateral cerebral strokes: a case report - Mein, Nils; Mammadli, Khadija; Luessi, Felix; Uphaus, Timo (Frontiers in Stroke, 2025)
A 21-year-old Caucasian woman was admitted to our neurologic intermediate care unit after attempting suicide by ingesting an estimated 15 g venlafaxine (Trevilor retard®), adding up to a serum concentration of approximately 17,943 μg/l. Brain magnetic resonance imaging (MRI) revealed bilateral cortical restricted-diffusion patterns, indicating ischemic lesions. We report a case of venlafaxine-induced serotonin syndrome most likely cumulating in diffuse artery vasospasm due to an autonomic effect mediated by the serotonergic and adrenergic systems, causing myocardial and cerebral injuries. The serotonin syndrome was treated symptomatically by administering fluids and benzodiazepines and managing the hyperthermia using paracetamol; also, medication with venlafaxine was stopped, and the hypoglycemia was treated. After 6 days, our patient was discharged to the psychiatric facility with no remaining neurologic deficit. The case report provides evidence of ischemic stroke as a rare adverse event of venlafaxine intoxication. Furthermore, we aim to increase awareness of hypoglycemia and epileptic seizures as complications of venlafaxine intoxication. In addition, we demonstrate important pitfalls in the diagnostic procedure and propose a treatment regimen for the underlying serotonin syndrome.